TALE-induced immunity against the bacterial blight pathogen Xanthomonas oryzae pv. oryzae in rice - Xiameng Xu; Ying Li; Zhengyin Xu; Jiali Yan; Yong Wang; Yijie Wang; Guanyun Cheng; Lifang Zou; Gongyou Chen (Phytopathology Research, 2022)
Abstract Transcription activator-like effectors (TALEs) are proteins produced by plant pathogenic Xanthomonas spp. TALEs exhibit a conserved structure and have the ability to directly bind to the promoter region of host target genes where they activate transcription. TALEs in Xanthomonas oryzae pv. oryzae (Xoo), the causal agent of bacterial blight (BB) in rice, play important roles in triggering resistance (ETI) and susceptibility (ETS) for rice immunity. This review briefly describes rice resistance breeding in China, TALE properties and their roles, BB resistance (R) and susceptibility (S) genes in rice, the arms-race between TALEs and TALE-targets, and strategies for breeding disease-resistant crops. A systematic overview of the complex roles of TALEs are presented along with ongoing efforts to breed crops with durable and broad-spectrum resistance to the pathogenic bacterium.